Analysis of the problem of increasing wear resistance of cutting tools - Диха, О.В.; Динько, О.П. (Problems of Tribology, 2016)
The basic approaches to tribo-mechanics of the process of wear of cutting tools on the basis of existing calculation-experimental methods of estimating the strength and speed of cutting. The constructive and technological methods of increasing the wear resistance of cutting part of cutting tool, defined way of choosing the optimal technology.